2007
DOI: 10.1007/s00271-007-0088-6
|View full text |Cite
|
Sign up to set email alerts
|

ET mapping for agricultural water management: present status and challenges

Abstract: Evapotranspiration (ET) is an essential component of the water balance. Remote sensing based agrometeorological models are presently most suited for estimating crop water use at both field and regional scales. Numerous ET algorithms have been developed to make use of remote sensing data acquired by sensors on airborne and satellite platforms. In this paper, a literature review was done to evaluate numerous commonly used remote sensing based algorithms for their ability to estimate regional ET accurately. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
179
0
10

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 328 publications
(210 citation statements)
references
References 94 publications
5
179
0
10
Order By: Relevance
“…Generally, researchers report SEBAL errors on daily ET estimation to range between 2% and about 35%. Gowda et al [25] reported an average accuracy of 85%, while Trezza [26] found the error to range from 2.7% to 35%, with 18.2% being the average error. Singh et al [9] found that ETc estimated using SEBAL could be within 5% of measured ETc.…”
Section: Resultsmentioning
confidence: 99%
“…Generally, researchers report SEBAL errors on daily ET estimation to range between 2% and about 35%. Gowda et al [25] reported an average accuracy of 85%, while Trezza [26] found the error to range from 2.7% to 35%, with 18.2% being the average error. Singh et al [9] found that ETc estimated using SEBAL could be within 5% of measured ETc.…”
Section: Resultsmentioning
confidence: 99%
“…The performance of the METRIC model has been tested by Gowda et al [60] in the Texas High Plains on two different days in 2005 using Landsat 5 TM data by comparison of resultant daily ET estimates with measured values derived from soil moisture budget. Integration of water balance model with METRIC estimated ET could provide significant improvements in the irrigation schedules as found in Spain by Santos et al [101].…”
Section: Mapping Evapotranspiration At High Resolution and With Intermentioning
confidence: 99%
“…Remote sensing based evapotranspiration estimation and its development has been reviewed from time to time [40,47,55]. This issue has been addressed from a hydrological perspective by Overgaard et al [58] with particular emphasis to plant sciences, agronomy, and irrigation applications [59,60]. Farahani et al [61] provide a focused survey of progress in crop evapotranspiration measurement and modeling with particular emphasis on the aspects of irrigational interest.…”
Section: Introductionmentioning
confidence: 99%
“…On global basis, the mean ET accounts for more than half of the total precipitation fallen on land surfaces (Chahine 1992;Oki and Kanae 2006). ET is also the major irrigation water and precipitation use on agricultural lands (Gowda et al 2008). ET rates are affected by many factors, such as ground solar radiation (GSR), wind speed, air temperature and humidity, soil water content, vegetation type, growth stage, planting density, and management practices, etc.…”
Section: Introductionmentioning
confidence: 99%
“…A substantial number of remote sensing algorithms, varied greatly in main assumptions and input requirements, have been proposed over the past few decades to provide ET mapping at different time and spatial scales (Jiang and Islam 2003;Gowda et al 2008;Kalma et al 2008;Li et al 2009;Jiménez et al 2011;Liou and Kar 2014). Remote sensed land surface temperature (LST) is the most critical input for many of those proposed algorithms.…”
Section: Introductionmentioning
confidence: 99%